The influence of health education through physical education on the healthy living behavior of elementary school students - Khairuddin, Khairuddin; Handayani, Sri Gusti; Jaslindo, Jaslindo; Masrun, Masrun (Jurnal Cakrawala Pendidikan, 2025)
This study evaluates the impact of integrating health education into physical education on healthy living behaviors of elementary students at State Elementary School SDN 48 Kuranji, Padang City. Employing a quasi-experimental design with a pretest-posttest control group, the study involved 60 students. The experimental group received health education integrated into physical education, while the control group followed standard physical education. Data collection used questionnaires and observations, analyzed through descriptive and inferential statistics, including paired t-tests. Results revealed significant improvements in knowledge, attitudes, and behaviors in the experimental group, with higher posttest scores than pretests, while the control group showed no notable changes. These findings underscore the effectiveness of combining health education with physical education to enhance health behaviors, supporting earlier research on the value of experiential learning. This study highlights the importance of a holistic educational approach to foster healthy lifestyles from an early age. Further research is recommended to assess long-term impacts and optimize program implementation in diverse educational settings.